Boosting 4th Graders’ Comprehension of Photosynthesis with Interactive Learning Videos - Dewi, Gusti Ayu Anggreni Puspita; Didith Pramunditya Ambara (International Journal of Elementary Education, 2025)
This study addresses the issue of the lack of innovative learning media for teaching Science, particularly the topic of photosynthesis, which can enhance student engagement and understanding. The limited availability of interesting and interactive resources in the classroom hinders the learning process of important concepts such as photosynthesis for 4th grade students. The aim of this research is to describe the design and development of a Discovery Learning-based Learning Video product, assess the quality of the Learning Video through expert evaluation, individual testing, and small group testing, and determine the effectiveness of the Discovery Learning-based Learning Video media. This research employs the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation), and data was collected through questionnaires, surveys, and tests. The data analysis techniques used were quantitative descriptive analysis and inferential statistics. The results of the study indicate that the Discovery Learning-based learning video, developed using Canva and Inshot applications, is accessible via YouTube/Drive links. Expert assessments resulted in scores of 92.5% from design experts, 97.5% from content/material experts, 93.18% from instructional design experts, and 92.5% from media experts. The individual test, involving three students, scored 94.16%, while the small group test, involving nine students, achieved a score of 93.88%, both categorized as excellent. The t-test result showed a value of 12.967, which is higher than the critical tvalue of 2.060 at a 5% significance level with 25 degrees of freedom. Therefore, H0 is rejected, and H1 is accepted, indicating that the average post-test score of students is higher than the BSKAP reference score. Thus, the Discovery Learning-based learning video has been proven effective in teaching the topic of photosynthesis to 4th grade students.